Case Study Literature Review (CSLR) The Effect of Boiled Basil and Turmeric on Vaginal Discharge in Adolescent Girls at SMAN 1 Sindangbarang, Cianjur Regency 2025 - Parmi Rahmayanti; Fenni Valianda Amelia Ramadhan; Putri Agus Febriyani; Ai Nurhayati Amalia Amalia; Dini Rinjani; Rika Puji Rustiwa; Tuti Nurhayati; Shinta Nurmallah; Rika Rustianti; Winwin Maulani (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2026)
Abstrack Vaginal discharge is a common condition experienced by women and can be physiological or pathological. Appropriate treatment is needed to reduce the severity of vaginal discharge and prevent further complications. This study aims to determine the effectiveness of interventions in reducing vaginal discharge levels in respondents based on changes in scores from the first visit to day 7. This study used an observational design with a pre-post approach without a control group. The study subjects consisted of four respondents who were measured at three times: the first visit, day 3, and day 7. Vaginal discharge was assessed using a score with categories: 0–5 normal/physiological, 6–10 mild vaginal discharge, 11–15 moderate vaginal discharge, and ≥16 pathological vaginal discharge. Analysis was performed by comparing the decrease in scores between the first visit and day 7. The results of the study show that in the first table there was a significant decrease in scores in all respondents, namely between 7–9 points, with a change in category from mild-moderate vaginal discharge to normal/physiological. Meanwhile, in the second table, the score decrease ranged from 3–6 points, and most respondents remained in the mild vaginal discharge category. Only one respondent achieved normal discharge. The conclusion of this study indicates that the intervention in the first group was more effective in reducing vaginal discharge levels than in the second group, as seen from the magnitude of the score decrease and the change in the category to normal discharge. Keywords: vaginal discharge, effectiveness, score decrease, women's reproductive health Reference: Journal (2021-2024)